Employment at will and employer liability - Mackey, Daniel Murnane (New York : American Management Association, 1986)
This publication surveys the volatile legal problems surrounding the discharge of an employee.
Introduction -- 1. Only in America: The historical background of the employer's right to fire an employee -- 2. There oughta be a law: major legislation limiting employers' rights in employment -- 3. Public policy: goliath begins to buckle -- 4. What happened to the Old-fashioned handshake? suits alleging breach of implied contract -- 5. Employee suits alleging personal injury as a result of discharge -- 6. Federal and state court forums, processes, and remedies.
Keywords: EMPLOYEE, DISMISSAL OF -- LAW AND LEGISLATION -- UNITED STATES